Kinematic reconstruction of the Raohe accretionary complex, Northeast China: Integration of onshore geologic evidence and global plate model. (January 2022) - Zhou, Zaizheng; Han, Zuozhen; Li, Sanzhong; Jiang, Zhaoxia; Li, Xiyao; Lan, Haoyuan
Abstract: The Raohe accretionary complex (RHC) is located at the eastern of northeast China and adjacent to Russian Far East. As a part of the Circum-Pacific Orogenic Belt, it is the unique region of the accretionary orogenic belt, which is associated with the subduction process of the Panthalassic-Pacific Plate (PPP). We synthesize the detrital zircon ages of terrigenous clastic rocks of the RHC and tectonic units along the East Asian Continental Margin (EACM) to clarify its provenance. Then we place the docking position of the RHC adjacent to the South China Block, and determine that the final accretion of the RHC occur during the later Late Jurassic (~150 Ma) according to combination for ages of stitching plutons and terrigenous clastic rock. Integrating with the published global-scale plate kinematic frame, we restored the pre-docking motion path of the RHC using the Gplates software. The reconstructed scenario shows that it is a long distance of at least 1000 km between the proto-RHC and continent margin when the basaltic volcanism occurred subaqueously within the abyssal basin of the PPP. This model also provides a probability that the proto-RHC and the proto-Yuejingshan accretionary complexes have the same drift history, before their simultaneous emplacement into the continental margin. Highlights: The Raohe accretionary complex accreted onto the southeast margin of the South China Block at ~150 Ma. The Middle Jurassic pillow basalts erupted subaqueously within the Izanagi plate. The Nadanhada Terrane is one geologic unit as relicts of oceanic crust and its overlayers.